Impact of Socio-Economic Changes on Economically Weak Children in English Language Teaching - Khanal, Hota Raj (Lumbini Journal of Language and Literature, 2022)
Children in schools are behaved on the basis of culture and economic status in which they are grown up. With the aim of exploring the impact of socio-cultural and economic aspects in schools on economically weak children in classroom teaching learning activities this study has been conducted based on the desktop study. This research designed title as Impact of Socio-Economic Changes on Economically Weak Children in English Language Teaching and collected data from the existing literature which are analyzed and reached in the conclusion that children from strong economic status and high cultural background will have better performance than the children who are from poor economic and low cultural background. Development of new technologies, social media highly help to mix up and transfer the culture as a result the direct impact of it is directly seen in the classroom. Change not only brings negative feelings it also tends to bring positive feelings. The change has challenged us (English language teachers) today so that to overcome this challenge we need to apply a balanced approach in the classroom so that we will be away from being boring teachers.